The politics of belonging in contemporary India : anxiety and intimacy - Chakraborty, Kaustav (Routledge, 2019)
"This volume looks at the emerging forms of intimacies in contemporary India. Drawing on rigorous academic research and pop culture phenomenon, the volume: - Brings together themes of nationhood, motherhood, disability, masculinity, ethnicity, kinship and sexuality and attempts to understand them within a more complex web of issues related to space, social justice, marginality and communication - Focuses on the struggles for intimacy by the disabled, queer, dalit, and other subalterns, as well as people with non-human intimacies to propose an alternative theory of the politics of belonging - Explores the role of social and new media in understanding and negotiating intimacies and anxieties Comprehensive and thought provoking, this book will be useful to scholars and researchers of political studies, sociology, sexuality and gender studies, women studies, cultural studies, and minority studies"--